Process for electroplating crude nickel

Through the synergistic effect of multi-step pretreatment and modified nano-silica, the problem of insufficient binding force of electroplating crude nickel plating is solved, and efficient bonding and performance improvement of the plating is achieved.

CN119530910APending Publication Date: 2025-02-28CHONGHUI SEMICON (JIANGMEN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411762376.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the existing electroplating crude nickel process, the outer plating layer is misaligned with the inner plating due to insufficient binding force, which affects the service life and wear resistance and corrosion resistance of the plating layer.

Method used

A multi-step pretreatment process is adopted, including alkaline solution oil removal, acid solution activation and zinc dipping, followed by step-by-step electroplating in a specific electroplating solution, and the binding force between the nickel layers is enhanced by using modified nanosilica.

Benefits of technology

It effectively improves the bonding force of the nickel layer, reduces the misalignment of the coating, extends the service life of the coating, and improves its wear resistance, corrosion resistance and electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168026020000071
    Figure BDA0005168026020000071
  • Figure BDA0005168026020000081
    Figure BDA0005168026020000081
Patent Text Reader

Abstract

The invention relates to the field of nickel electroplating, and particularly discloses a process for electroplating crude nickel. Comprising the following steps that a workpiece is immersed in an alkaline solution for surface chemical oil removal; immersing the cleaned workpiece into an acid solution to activate the surface of the workpiece; the workpiece subjected to bright dipping treatment is soaked in a mixed solution of sodium hydroxide, zinc oxide, tartrate, ferric chloride and sodium nitrate, and the surface of the workpiece is covered with a zinc layer; the activated workpiece is used as a cathode, and in a mixed solution A of nickel sulfate, sodium chloride, sodium sulfate, sodium laureth sulfate and polysarcosine, current is introduced into the cathode, so that a uniform nickel layer A is deposited on the surface of the workpiece; adding the modified nano silicon dioxide into the mixed solution A to form a mixed solution B, and introducing current into a cathode, so that a uniform nickel layer B is deposited on the surface of the cathode; according to the method, the mechanical property of an existing electroplating coarse nickel coating can be effectively improved, and meanwhile the service life of the coating on the surface of a workpiece is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nickel electroplating, and more particularly to a process for electroplating rough nickel. Background Art

[0002] As a common metal surface treatment technology, nickel electroplating is mainly aimed at enhancing the corrosion resistance of the metal material surface and improving the quality level of its appearance. This treatment process can form a uniform and smooth nickel layer on the metal surface, thereby protecting the inside of the metal from corrosion and extending the service life. Among them, electroplating rough nickel, as a way of electroplating nickel, refers to depositing a thicker nickel layer on the metal surface through an electroplating process. This process can further improve the wear resistance and corrosion resistance of the metal. At present, rough nickel electroplating is commonly used for surface treatment of materials such as steel, zinc alloy, aluminum alloy and copper alloy.

[0003] The existing basic process of electroplating rough nickel mainly includes the steps of preparing the plating solution, pretreatment of the workpiece, electroplating process and post-treatment of the workpiece. In the electroplating process, the rough nickel ions need to be reduced and deposited on the surface of the workpiece by the action of a DC power supply, and the desired rough nickel layer is formed on the surface of the workpiece.

[0004] However, since the electroplating rough nickel process requires the formation of a thicker nickel layer on the metal workpiece, the outer coating is easily misaligned with the inner coating due to insufficient bonding force, which affects the service life of the electroplated rough nickel coating and is not conducive to improving the wear resistance and corrosion resistance of the workpiece surface. Summary of the invention

[0005] In order to effectively improve the mechanical properties of the existing electroplated rough nickel coating itself and extend the service life of the coating on the workpiece surface, the present application provides a process for electroplating rough nickel.

[0006] The present application provides a process for electroplating rough nickel, which adopts the following technical solution: A process for electroplating rough nickel comprises the following steps: Cleaning: Immerse the workpiece in an alkaline solution for surface chemical degreasing; Lighting: Immerse the cleaned workpiece in an acid solution to activate its surface; Activation: Immerse the workpiece after light treatment in a mixed solution of sodium hydroxide, zinc oxide, tartrate, ferric chloride and sodium nitrate to cover the surface of the workpiece with a zinc layer; Primary nickel plating: the workpiece after activation treatment is used as the cathode, and current is passed into the cathode in a mixed solution A of nickel sulfate, sodium chloride, sodium sulfate, sodium laureth sulfate and polysarcosine to deposit a uniform nickel layer A on its surface; Secondary nickel plating: Add modified nano-silica to mixed solution A to form mixed solution B, and pass current into the cathode to deposit a uniform nickel layer B on its surface.

[0007] By adopting the above technical scheme, the effects of differences in expansion coefficients of electroplated workpiece materials and different material compositions on the bonding strength of the plating layer are effectively solved by using the alkaline corrosion degreasing, polishing, activated zinc immersion and other treatment methods used in the pre-treatment process; at the same time, the electroplated workpiece material is directly subjected to secondary nickel electroplating after the above multi-step pre-treatment, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; the sodium lauryl polyether sulfate and polysarcosine composite nickel electroplating solution used has stable solution composition, good dispersibility, a wide pH range close to neutrality, less corrosion to the surface of the electroplated workpiece material itself, and effectively reduces the corrosion of the electroplated workpiece material during the nickel electroplating process; Among them, the technical solution of the present application covers the surface of the workpiece with a coating by step-by-step electroplating, so that the inner nickel layer can first form a thicker and more strongly bonded basic coating on the surface of the electroplated workpiece, and then form an outer coating on the surface of the inner basic coating through the synergistic effect of modified nano-silicon dioxide. The modified nano-silicon dioxide is used to effectively enhance the bonding force between the basic coating and the outer coating, so as to form a dense and smooth electroplating layer on the surface of the workpiece, reduce the dislocation between the basic coating and the outer coating due to insufficient bonding force of metal atoms, and thus enhance the wear resistance, corrosion resistance and electrical conductivity of the rough nickel coating of the present application, so as to achieve the purpose of extending the service life of the rough nickel coating on the surface of the electroplated workpiece.

[0008] Optionally, the pretreatment step of modified nano-silica includes: adding polyvinyl alcohol fiber and sodium hexametaphosphate to a solvent, heating and stirring, mixing evenly to obtain a mixture A, then adding the nano-silica to be pretreated and modified to the mixture A to form a mixture B, heating and stirring to react, filtering out, and then washing with water and drying to obtain the pretreated modified nano-silica.

[0009] By adopting the above technical scheme, polyvinyl alcohol fiber and sodium hexametaphosphate are used to modify nano-silicon dioxide, so that the modified nano-silicon dioxide can better provide a synergistic effect on the rough nickel plating in the electroplating solution, thereby achieving the purpose of improving the mechanical properties of the rough nickel plating itself while also improving the overall bonding strength of the rough nickel plating with the workpiece surface.

[0010] Optionally, the solution components used for activation include: 63-70 parts of sodium hydroxide, 18-24 parts of zinc oxide, 16-19 parts of tartrate, 2-4 parts of ferric chloride and 3-5 parts of sodium nitrate.

[0011] By adopting the above technical scheme, sodium hydroxide can maintain the pH value of the solution system, so that the electroplating process can be carried out in a suitable chemical environment, and can be used as a stabilizer in the electroplating solution to help improve the quality and adhesion of the coating. At the same time, tartrate as a chelating agent helps to stabilize metal ions, making the electroplating process more uniform and controllable, and improving the molding quality of the coating. In addition, ferric chloride and sodium nitrate can stabilize the redox potential of the solution, which helps to promote the electroplating reaction.

[0012] Optionally, the solution components used for the primary nickel plating include: 150-190 parts of nickel sulfate, 13-18 parts of sodium chloride, 83-96 parts of sodium sulfate, 20-26 parts of sodium lauryl polyether sulfate and 16-22 parts of polysarcosine.

[0013] By adopting the above technical solution, after power is turned on, the sodium chloride in the system can activate the nickel anode and increase the dissolution of nickel ions in the electroplating solution, while the sodium sulfate in the system can enhance the activity of electrons in the electroplating solution, thereby allowing the nickel ions in the system to quickly gather on the surface of the cathode workpiece. At the same time, the synergistic effect of sodium lauryl polyether sulfate and polysarcosine can help improve the molding quality and uniformity of the coating surface, thereby effectively reducing the gas pinholes and pitting on the coating surface.

[0014] Optionally, the solution components used for the secondary nickel plating include: 12 to 15 parts of polyvinyl alcohol fiber, 23 to 30 parts of sodium hexametaphosphate and 16 to 22 parts of nano silicon dioxide.

[0015] By adopting the above technical scheme, the polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silica can work synergistically with each other. Sodium hexametaphosphate is combined with the hydroxyl group on the surface of nano-silica to form a complex, which increases the repulsive force between the nano-silica particles, so that the nano-silica particles can be more fully dispersed in the electroplating solution. At the same time, the anions ionized by sodium hexametaphosphate in the system are adsorbed on the surface of the polyvinyl alcohol fiber, which increases the negative charge on the surface of the polyvinyl alcohol fiber. The sodium ions ionized by sodium hexametaphosphate increase the thickness of the double electric layer, so as to better increase the dispersion effect of the polyvinyl alcohol fiber in the system, and then better extend the polyvinyl alcohol fiber between the double coatings, so as to achieve the purpose of improving the connection strength between the nickel layer A and the nickel layer B, which helps to better improve the wear resistance and corrosion resistance of the rough nickel coating.

[0016] Optionally, the diameter of the polyvinyl alcohol fiber is 18 to 25 μm.

[0017] Optionally, the particle size of the sodium hexametaphosphate is 60-80 mesh.

[0018] Optionally, the particle size of the nano-silicon dioxide is 10 to 15 nm.

[0019] By adopting the above technical solution and selecting polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silicon dioxide materials with specific parameters, the compounding effect of the three in the solution can be further optimized, so that a rough nickel plating with better wear resistance, corrosion resistance and conductivity can be obtained on the surface of the workpiece.

[0020] Optionally, the solution used for the secondary nickel plating further comprises: 18 to 22 parts of nanocellulose.

[0021] By adopting the above technical solution, nanocellulose can form a three-dimensional network structure in the coating, which facilitates the movement of nanosilicon dioxide and conductive particles in the coating, thereby more effectively improving the overall wear resistance and conductivity of the rough nickel layer.

[0022] In summary, this application has the following beneficial effects: 1. The present application utilizes the alkali corrosion degreasing, polishing, activation zinc dipping and other treatment methods adopted in the pre-treatment process to effectively solve the influence of the difference in expansion coefficient of the electroplated workpiece material and the different material composition on the bonding strength of the plating layer; at the same time, the electroplated workpiece material is directly subjected to secondary nickel electroplating after the above multi-step pre-treatment, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; the sodium lauryl polyether sulfate and polysarcosine composite nickel electroplating solution adopted has stable solution composition, good dispersibility, a wide pH value range close to neutral, less corrosion to the surface of the electroplated workpiece material itself, and effectively avoids the corrosion of the electroplated workpiece material during the nickel electroplating process; in addition ... pre-treatment, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; in addition, the electroplated workpiece material is directly subjected to secondary nickel plating, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; in addition, the electroplated workpiece material is directly subjected to secondary nickel plating, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; in addition, the electroplated workpiece material is directly subjected to secondary nickel plating, without the need for chemical nickel plating or cyanide copper plating, and the operation process is simple; in addition, the electroplated work The workpiece surface is coated by a step-by-step electroplating method, so that the inner nickel layer first forms a thicker and more strongly bonded base coating on the surface of the electroplated workpiece, and then forms an outer coating on the surface of the inner base coating through the synergistic effect of modified nano-silicon dioxide. The modified nano-silicon dioxide is used to effectively improve the bonding force between the base coating and the outer coating, so as to form a dense and smooth electroplating layer on the workpiece surface, reduce the dislocation between the base coating and the outer coating due to insufficient bonding force of metal atoms, and further enhance the wear resistance, corrosion resistance and electrical conductivity of the rough nickel coating of the present application, so as to achieve the purpose of extending the service life of the rough nickel coating on the surface of the electroplated workpiece; 2. The present application enables polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silica to work synergistically with each other. Sodium hexametaphosphate is used to combine with the hydroxyl group on the surface of nano-silica to form a complex, thereby increasing the repulsive force between the nano-silica particles, so that the nano-silica particles can be more fully dispersed in the electroplating solution. At the same time, the anions ionized by sodium hexametaphosphate in the system are adsorbed on the surface of the polyvinyl alcohol fiber, thereby increasing the negative charge on the surface of the polyvinyl alcohol fiber. The sodium ions ionized by sodium hexametaphosphate are used to increase the thickness of the double electric layer, so as to better increase the dispersion effect of the polyvinyl alcohol fiber in the system, and then better extend the polyvinyl alcohol fiber between the double coatings, thereby achieving the purpose of improving the connection strength between the nickel layer A and the nickel layer B, which helps to better improve the wear resistance and corrosion resistance of the rough nickel coating. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0024] Preparation Example 1 Preparation method of pretreated modified nano-silica: Weigh 12 g of polyvinyl alcohol fiber and 30 g of sodium hexametaphosphate according to the weight ratio, add them into 1 L of water, heat to 70° C., stir and mix well to obtain a mixture A; 16 g of nano-silicon dioxide was added to mixture A to form mixture B, and the mixture was heated to 80° C., stirred for reaction for 30 min, filtered out, washed with water, and dried to obtain pretreated modified nano-silicon dioxide.

[0025] The diameter of the polyvinyl alcohol fiber is 30-35 μm, and the CAS number is 9002-89-5; the particle size of the sodium hexametaphosphate is 40-50 mesh; the particle size of the nano-silicon dioxide is 20-25 nm; and the aluminum alloy is 6061-T6.

[0026] Preparation Example 2 The preparation method of pre-treated modified nano silicon dioxide comprises the following steps: Step 1: 15 g of polyvinyl alcohol fiber and 23 g of sodium hexametaphosphate were weighed and added into 1 L of water, the temperature was raised to 70° C., and the mixture was stirred and mixed to obtain a mixture A; Step 2: Add 22 g of nano-silica to mixture A to form mixture B, heat to 80° C., stir and react for 30 min, filter out, wash with water, and dry to obtain pretreated modified nano-silica.

[0027] The diameter of the polyvinyl alcohol fiber is 30-35 μm, and the CAS number is 9002-89-5; the particle size of the sodium hexametaphosphate is 40-50 mesh; the particle size of the nano-silicon dioxide is 20-25 nm; and the aluminum alloy is 6061-T6.

[0028] Preparation Example 3 The difference from Preparation Example 2 is that the diameter of the polyvinyl alcohol fiber is 18 to 25 μm.

[0029] Preparation Example 4 The difference from Preparation Example 2 is that the particle size of sodium hexametaphosphate is 60-80 mesh.

[0030] Preparation Example 5 The difference from Preparation Example 2 is that the particle size of the nano-silicon dioxide is 10 to 15 nm.

[0031] Preparation Example 6 The difference from Preparation Example 2 is that in step 2, 22 g of nanocellulose is also added, wherein the diameter of the nanocellulose is 5 to 10 nm.

[0032] Examples 1 to 6 A process for electroplating rough nickel is prepared by the following steps: Cleaning: Immerse the aluminum alloy workpiece in an alkaline solution of 5g / L sodium hydroxide, 40g / L sodium carbonate decahydrate, 50g / L sodium phosphate, and 0.5g / L sodium silicate at 50°C for 1 minute to chemically degrease the surface; Polishing: After the aluminum alloy workpiece has been degreased and cleaned, it is first cleaned with hot water and running cold water, and then immersed in a solution of 60% nitric acid and 20% hydrofluoric acid by volume for 1.5 minutes at room temperature to remove the surface oxide scale of the aluminum alloy workpiece; Activation: Immerse the aluminum alloy workpiece after the light treatment in a mixed solution of 70g / L sodium hydroxide, 24g / L zinc oxide, 16g / L tartrate, 2g / L ferric chloride and 3g / L sodium nitrate at 15°C for 1 minute to evenly deposit a complete zinc layer on the surface of the aluminum alloy workpiece; Primary nickel plating: The activated aluminum alloy workpiece is used as the cathode and placed in a mixed solution A of 150 g / L nickel sulfate, 18 g / L sodium chloride, 96 g / L sodium sulfate, 26 g / L sodium lauryl polyether sulfate and 16 g / L polysarcosine at pH 7.2 at 15°C. 2 A current with a cathode current density of 1.50 μm was passed through the plate and electroplated for 20 min, so that a nickel layer A with a thickness of 40 μm was deposited on the surface of the plate; Secondary nickel plating: Add modified nano-silica to mixed solution A to form mixed solution B, and add 1A / dm 2 A current with a cathode current density of is passed and electroplating is performed for 10 minutes, so that a nickel layer B with a thickness of 10 μm is deposited on the surface of the aluminum alloy workpiece, thereby obtaining an aluminum alloy workpiece with rough nickel electroplating on the surface.

[0033] The modified nano-silicon dioxide in the secondary nickel plating process is the nano-silicon dioxide prepared in Preparation Examples 1 to 6.

[0034] Embodiments 7 to 12 A process for electroplating rough nickel is prepared by the following steps: Cleaning: Immerse the aluminum alloy workpiece in an alkaline solution of 5g / L sodium hydroxide, 40g / L sodium carbonate decahydrate, 50g / L sodium phosphate, and 0.5g / L sodium silicate at 50°C for 1 minute to chemically degrease the surface; Polishing: After the aluminum alloy workpiece has been degreased and cleaned, it is first cleaned with hot water and running cold water, and then immersed in a solution of 60% nitric acid and 20% hydrofluoric acid by volume for 1.5 minutes at room temperature to remove the surface oxide scale of the aluminum alloy workpiece; Activation: Immerse the aluminum alloy workpiece after the light treatment in a mixed solution of 63g / L sodium hydroxide, 18g / L zinc oxide, 19g / L tartrate, 4g / L ferric chloride and 5g / L sodium nitrate at 15°C for 1 minute to evenly deposit a complete zinc layer on the surface of the aluminum alloy workpiece; Primary nickel plating: The activated aluminum alloy workpiece is used as the cathode and placed in a mixed solution A of 190 g / L nickel sulfate, 13 g / L sodium chloride, 83 g / L sodium sulfate, 20 g / L sodium laureth sulfate and 22 g / L polysarcosine at pH 7.2 at 15°C. 2 A current with a cathode current density of 1.50 μm was passed through the plate and electroplated for 20 min, so that a nickel layer A with a thickness of 40 μm was deposited on the surface of the plate; Secondary nickel plating: Add modified nano-silica to mixed solution A to form mixed solution B, and add 1A / dm 2 A current with a cathode current density of is passed and electroplating is performed for 10 minutes, so that a nickel layer B with a thickness of 10 μm is deposited on the surface, thereby obtaining an aluminum alloy workpiece with rough nickel electroplating on the surface.

[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that the polyvinyl alcohol fiber is replaced by an equal amount of carboxymethyl cellulose fiber, wherein the carboxymethyl cellulose fiber has a diameter of 30 to 35 μm and a CAS number of 9000-11-7.

[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that sodium hexametaphosphate is replaced by an equal amount of sodium citrate.

[0037] Comparative Example 3 The difference between this comparative example and Example 1 is that the nano silicon dioxide is replaced by an equal amount of nano zirconium dioxide, wherein the particle size of the nano zirconium dioxide is 20-25 nm.

[0038] Comparative Example 4 The difference between this comparative example and Example 1 is that the polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silicon dioxide are all replaced by equal amounts of nano-silicon dioxide.

[0039] Performance testing 1) Thickness test The aluminum alloy workpieces prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were cut into 5 cm 3 The samples were placed in an ellipsometer for thickness measurement. The smaller the change in the thickness of the electroplating layer at multiple positions in the sample, the better the overall uniformity of the electroplating layer of the aluminum alloy workpiece. Among them, if the thickness distribution of the electroplating layer is uniform, it is recorded as "excellent", and if the thickness distribution is uneven, it is recorded as "poor".

[0040] 2) Adhesion test The aluminum alloy workpieces prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were cut into 5 cm 3 The samples are taken, and then according to "GB / T 5270-2005 Test method for adhesion strength of electrodeposited and chemically deposited metal coatings on metal substrates", a tensile test is performed on multiple samples separately. The stretching is stopped when cracks appear on the surface of the sample, and the tensile force value (Mpa) of the tensile testing machine is recorded at this time. The larger the tensile force value, the better the overall wear resistance of the electroplating layer.

[0041] 3) Corrosion resistance test The aluminum alloy workpieces prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were cut into 5 cm 3 For the samples, the thickness at multiple positions was measured by ellipsometer, and the average value was taken and recorded as a1. The samples were then immersed in 98% concentrated sulfuric acid for 2 hours. After being taken out, the thickness at multiple positions was measured by ellipsometer, and the average value was taken and recorded as a2. The thickness difference (μm) before and after immersion of multiple samples a1-a2 was calculated. The smaller the thickness difference, the better the corrosion resistance of the electroplated layer of the aluminum alloy workpiece.

[0042] 4) Conductivity test The aluminum alloy workpieces prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were cut into 5 cm 3 According to GB / T 12966-2022 Eddy Current Test Method for Electrical Conductivity of Aluminum and Aluminum Alloys, the electrical conductivity (%) IACS of multiple samples at room temperature is tested. The higher the conductivity value, the better the conductivity of the electroplating layer of the aluminum alloy workpiece.

[0043] Table 1 - Summary of test data of Examples 1 to 12 and Comparative Examples 1 to 4 By comparing the test data of Example 1 and Comparative Example 4 in Table 1, it can be seen that the electroplated layer of the aluminum alloy workpiece prepared according to the technical solution of the present application has greatly improved wear resistance, corrosion resistance and electrical conductivity compared to the electroplated layer of the existing aluminum alloy workpiece without adding polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silicon dioxide, and while effectively optimizing the various properties of the existing electroplated rough nickel aluminum alloy workpiece, the thickness uniformity of the electroplated layer of the aluminum alloy workpiece can also be effectively improved, thereby achieving the purpose of extending the service life of the electroplated rough nickel layer of the present application on the surface of the aluminum alloy workpiece through the various mechanical properties of the electroplated rough nickel layer; In addition, by comparing the experimental data of Example 1 and Comparative Examples 1 to 3, it can be seen that if the synergistic effect of polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silicon dioxide is destroyed in the system, the wear resistance, corrosion resistance, electrical conductivity and uniformity of the rough nickel electroplating layer of the prepared aluminum alloy workpiece will be reduced to varying degrees, indicating that the three are indispensable in the electroplating solution of the technical solution of the present application, thereby indicating that the surface properties of the modified nano-silicon dioxide are effectively improved, and then the nano-silicon dioxide can better extend and diffuse in the rough nickel electroplating layer through the synergistic effect with polyvinyl alcohol fiber and sodium hexametaphosphate. Therefore, the prerequisite for improving the performance of the rough nickel electroplating layer of the aluminum alloy workpiece of the present application is the synergistic cooperation of the three to obtain a more effective synergistic effect on the rough nickel electroplating layer of the aluminum alloy workpiece.

[0044] By comparing the test data of Examples 1 to 2 and Examples 7 to 8 in Table 1 respectively, it can be seen that when the inventor controls the weight ratio of polyvinyl alcohol fiber, sodium hexametaphosphate and nano-silicon dioxide in the electroplating solution, the wear resistance, corrosion resistance and conductivity of the rough nickel electroplating layer of the aluminum alloy workpiece of the present application can be better improved, thereby achieving the purpose of further improving the service life of the rough nickel electroplating layer prepared in the present application on the surface of the aluminum alloy workpiece.

[0045] By comparing the test data of Examples 2 to 5 and Examples 8 to 11 in Table 1, it can be seen that when the inventors use polyvinyl alcohol fibers, sodium hexametaphosphate and nano-silicon dioxide with specific physical parameters for addition, the adhesion performance and conductivity of the rough nickel electroplating layer of the aluminum alloy workpiece of the present application can be further enhanced, and at the same time, the thickness difference before and after corrosion can be more effectively reduced, thereby more effectively improving the service life and application range of the aluminum alloy workpiece of the present application.

[0046] By comparing the test data of Examples 2 and 6 and Examples 8 and 12 in Table 1, it can be seen that when the inventor selects a specific amount and diameter of nanocellulose to supplement the electroplating solution, it can be clearly seen that the wear resistance, corrosion resistance and electrical conductivity of the rough nickel electroplating layer of the aluminum alloy workpiece of the present application are enhanced to a greater extent, thereby enabling the rough nickel plating layer of the aluminum alloy workpiece prepared by the present application to be further improved in terms of service life and application range, and has great economic value.

[0047] By comparing the experimental data of Examples 1 and 7 in Table 1, it can be seen that when the inventors select an activation mixture with a specific weight ratio to treat the surface of the aluminum alloy workpiece in the activation step, the rough nickel electroplating layer of the aluminum alloy workpiece is greatly enhanced in wear resistance, corrosion resistance and electrical conductivity, which indicates that the surface of the activated aluminum alloy workpiece can be better combined with the rough nickel electroplating layer, further improving the service life of the rough nickel electroplating layer on the surface of the aluminum alloy workpiece.

[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for electroplating rough nickel, characterized in that: The following steps are involved: Cleaning: Immerse the workpiece in an alkaline solution for surface chemical degreasing; Lighting: Immerse the cleaned workpiece in an acid solution to activate its surface; Activation: Immerse the workpiece after light treatment in a mixed solution of sodium hydroxide, zinc oxide, tartrate, ferric chloride and sodium nitrate to cover the surface of the workpiece with a zinc layer; Primary nickel plating: the workpiece after activation treatment is used as the cathode, and current is passed into the cathode in a mixed solution A of nickel sulfate, sodium chloride, sodium sulfate, sodium laureth sulfate and polysarcosine to deposit a uniform nickel layer A on its surface; Secondary nickel plating: Add modified nano-silica to mixed solution A to form mixed solution B, and pass current into the cathode to deposit a uniform nickel layer B on its surface.

2. A process for electroplating rough nickel according to claim 1, characterized in that: The pretreatment step of modified nano-silica includes: adding polyvinyl alcohol fiber and sodium hexametaphosphate to a solvent, heating and stirring, mixing evenly to obtain a mixture A, then adding the nano-silica to be pretreated and modified to the mixture A to form a mixture B, heating and stirring to react, filtering out, and then washing with water and drying to obtain the pretreated modified nano-silica.

3. A process for electroplating rough nickel according to claim 1, characterized in that: The solution components used for activation include: 63-70 parts of sodium hydroxide, 18-24 parts of zinc oxide, 16-19 parts of tartrate, 2-4 parts of ferric chloride and 3-5 parts of sodium nitrate.

4. A process for electroplating rough nickel according to claim 1, characterized in that: The solution components used for the primary nickel plating include: 150-190 parts of nickel sulfate, 13-18 parts of sodium chloride, 83-96 parts of sodium sulfate, 20-26 parts of sodium lauryl polyether sulfate and 16-22 parts of polysarcosine.

5. A process for electroplating rough nickel according to claim 4, characterized in that: The solution components used for secondary nickel plating include: 12-15 parts of polyvinyl alcohol fiber, 23-30 parts of sodium hexametaphosphate and 16-22 parts of nano silicon dioxide.

6. A process for electroplating rough nickel according to claim 5, characterized in that: The diameter of the polyvinyl alcohol fiber is 18-25 μm.

7. A process for electroplating rough nickel according to claim 5, characterized in that: The particle size of the sodium hexametaphosphate is 60-80 mesh.

8. A process for electroplating rough nickel according to claim 5, characterized in that: The particle size of the nano silicon dioxide is 10-15 nm.

9. A process for electroplating rough nickel according to claim 5, characterized in that: The solution components used in the secondary nickel plating also include: 18 to 22 parts of nanocellulose.

Citation Information

Patent Citations

  • Electroless nickel plating method of aluminum

    JP1996158060A

  • Composite plating liquid, plating method and particle dispersion method

    JP2014148719A

  • Composite plated material, and method of producing the same

    JP2021008670A

  • Method for Electrochemically Depositing a Metal on a Substrate

    US20110132766A1